Structured Representation of Pre-Defined Information Backflow in Standards and Directives - Max Layer; Janosch Luttmer; Arun Nagarajah; Ralph Stelzer (Standards, 2024)
This publication examines the representation of information within test specifications and formulas defined in standards and directives. This information often pre-defines not only the tests and requirements to be conducted but also the information backflow within the execution. These results are crucial for the effective management of knowledge throughout the product development process as well as for the creation and maintenance of digital representations of a physical product or plant. However, the accessibility of this information is frequently hindered by its extensive and heterogenous definition across a multitude of standards, directives, and other technical regulations. Furthermore, the pre-defined information is typically documented and processed manually on a recurring basis. Given this challenge, the following article presents a holistic two-part approach for pre-defining the information backflow of subsequent physical instances. Initially, an analysis of multiple test specifications in standards and directives is conducted, resulting in the development of a generic data model to represent this Pre-defined Information Backflow (PdIB). The second step builds on the first and defines an optimized representation for machine readability and executability for the future design of standards and directives. The two parts are brought together and validated using representative examples, thereby demonstrating the practical applicability and effectiveness of the proposed approach. This enhances the accessibility and usability of information in test specifications and formulas, thereby establishing a foundation for enhancing the efficiency of knowledge work in product development and the creation of digital representations of products and plants.